KG-ML Approach Image Recognition for Cultural Heritage. - Câmara, A.; de Almeida, A.; Oliveira, J. (Poster published: Ciencia 2022 - Science and Technology in Portugal Summit, 2022)
Populate a Knowledge-Graph (KG) following the CIDOC-CRM guidelines and extend it to develop a knowledge base able to support a Machine Learning (ML) based system for image recognition and classification of immovable cultural heritage of small dimensions. This hybrid method shall be applied to detect dolmens from satellite images, showing how this methodology works and establishing its value as a viable alternative for traditional prospection fieldwork in archaeology.